The acinar regulator Gata6 suppresses KrasG12V-driven pancreatic tumorigenesis in mice. Issue 3 (16th January 2015) - Martinelli, Paola; Madriles, Francesc; Cañamero, Marta; Pau, Enrique Carrillo-de Santa; Pozo, Natalia del; Guerra, Carmen; Real, Francisco X
Abstract : Background and aims: Gata6 is required to complete and maintain acinar differentiation in the mouse pancreas. Pancreas-specific Gata6 ablation during development causes extensive and persistent acinar-ductal metaplasia, which is considered an initial step of mutant KRas -driven carcinogenesis. Therefore, the Gata6 -null pancreas might represent a tumour-prone environment. We investigated whether Gata6 plays a role during pancreatic tumorigenesis. Design: We analysed genetically engineered mouse models and human pancreatic ductal adenocarcinoma (PDAC) cell lines, using a combination of histopathological studies, genome-wide expression and chromatin immunoprecipitation experiments to understand the role of Gata6 in the initiation and progression of KRas G12V -driven tumours Results: We show that Gata6 maintains the acinar differentiation programme, both directly and indirectly, and it concomitantly suppresses ectopic programmes in the pancreas. Gata6 ablation renders acinar cells more sensitive to KRas G12V, thereby accelerating tumour development. Gata6 expression is spontaneously lost in a mouse model of KRas G12V -driven PDAC, in association with altered cell differentiation. Using a combination of ChIP-Seq and RNA-Seq, we show that Gata6 exerts its tumour-suppressive effect through the promotion of cell differentiation, the suppression of inflammatory pathways, and the direct repression of cancer-related pathways. Among them is the epidermal growth factor receptor (EGFR) pathway, the activity of which is upregulated in the normal and preneoplastic Gata6 -null pancreas. Accordingly, GATA6-silencing in human PDAC cells leads to an upregulation of EGFR. Conclusions: We propose that, in the pancreas, Gata6 acts as a tumour suppressor by enforcing acinar cell differentiation, by directly and indirectly repressing ectopic differentiation programmes, and by regulating crucial cancer-related gene expression pathways.